PSIKOLOGI SUFISTIK (Studi atas Pemikiran Sachiko Murata dalam Buku The Tao of Islam) - Erni Susilawati (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
Sachiko Murata has developed many discourses of spiritual psychology asmentioned in her book The Tao of Islam. The writer found that the higheststage of Sufi which is to be united with God exists vertically betweenthe spirit, soul, mind and heart. Spirit is described as the highest innerdimension, which is connected to soul, as a part of the physical or bodystructure. The relationship between the soul and spirit raises other innerdimension that is the mind and heart. For a Sufi who has reached perfectionor sanctity of life, it also means to have a harmonious relationship betweenman's inner dimension, namely the achievement of happiness and peace ofmind which is reflected in real behavior. This is what Murata stated about ahealthy soul, a soul which is strongly influenced by the spirit or goodness.